Investigation of structure and electrical hysteresis in functional materials - Beilsten-Edmands, J (2017)
This thesis addresses issues regarding structure and electrical hysteresis in two functional materials; the semiconductor CH3NH3PbI3, which is the prototypical material used in lead-halide perovskite solar cells, and the magnetic multiferroic CuFeO2. Thin film CH3NH3PbI3 is characterised by electrical hysteresis loop measurements which show that the current-voltage hysteresis observed in lead-halide perovskite solar cells cannot be attributed to a ferroelectric nature of the material but instead indicate a conductive hysteretic mechanism. This is further investigated through dielectric spectroscopy of crystals of CH3NH3PbI3 and CH3NH3PbBr3, which reveal dispersive, thermally activated hopping conduction due to ionic vacancy conduction. The low activation energies reveal that ionic vacancy migration is the likely underlying mechanism of current-voltage hysteresis. The structural details of CH3NH3PbI3 are investigated by X-ray and neutron scattering. X-ray diffraction gives no indication of a polar crystal structure at room temperature and the extent of symmetry twinning is characterised. Quasielastic neutron scattering on crystals of CH3NH3PbI3 is used to study the rotational dynamics of the CH3NH3 molecule, resolved in q-space. This reveals the highly isotropic nature of CH3NH3 molecular reorientation throughout the tetragonal phase. In the multiferroic material CuFeO2, a ferroelectric polarisation memory effect is characterised through history-dependent pyrocurrent measurements. Uniaxial strain is applied to control the magneto-structural domain population, however the polarisation memory is found to only depend on the magnetic history of the material. Simulations of the magnetic domain wall spin structures by Monte Carlo methods predict the existence of helical domain walls in the magnetic ground state. It is proposed that these helical domain walls can act to store information on the helical state of the ferroelectric phase, thus accounting for the observed memory effects.